Mining and Structural Poverty of Islet Community (A Case Study of Community Sarakaman, Kotabaru, South Kalimantan) - Hakim, Lukman; A. Kinseng, Rilus (Sodality: Jurnal Sosiologi Pedesaan, 2015)
This research was conducted in the village of Sarakaman, District of Sebuku Island, Kotabaru, South Kalimantan. There are two mining industry corporations in Sebuku Island. They are PT Bahari Cakrawala Sebuku (PT BCS) and PT Sebuku Iron Lateritic Ores (PT SILO). PT BCS was established since 1997 and PT SILO was established 2004. In 2010 PT BCS and PT SILO expand the exploitation area in Sarakaman. Sarakaman community was the subject of this research. The purpose of this research were: (1) To analyze the process of mining industrialization in Sebuku Island and (2) To analyze the dynamics of the community poverty as the impact of mining industrialization in Sebuku Island. The data were collected through participant observation, indepth interviews, focus group discussions, the study of literature/documents and participation in community activities. This research concluded: (1) permits of mining industry corporations given by local government without local communities agreement, (2) compensation of land acquisition and residential communities conducted by mining industry corporations was fairly large, but not comparable to the community socio-economic sustainability, (3) Acquisition of land and residential communities by mining industry corporations reduce the accessibility of resources agrarian society, (4) in limited of agrarian resource access, the community survive with their livelihood strategies, (5) environmental damage as the effect of the mining industry activities make difficult the activity and subsistence of communities. Key words: accessibility, islet community, mining industrialization, structural poverty